DECODING LITERACY: INOVASI LKPD BERBASIS GAME CODING MENGGUNAKAN CANVA UNTUK MENSTIMULUS KEMAMPUAN SINTAKSIS DAN COMPUTATIONAL THINKING PADA PESERTA DIDIK KELAS 2 SEKOLAH DASAR - Andikayana, Dewa Made; Karopak, Julsari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is aimed to developed a game coding-based Student Worksheet (LKPD) titled Decoding Literacy using Canva for Education, conducted at SDN 33 Kendari from January 8 to March 3, 2026. The LKPD features a four-level hierarchical architecture (Assembling Letters, Assembling Syllables, Assembling Words, and Assembling Sentences) with twelve missions integrating syntactic competence and computational thinking (CT) for Grade 2 students. The study addressed four objectives: (1) content validity by four expert validators using Aiken V (minimum threshold V ≥ 0.88 based on the Aiken V table for n=4 raters) calculated manually in Microsoft Excel across 12 mission items; (2) small-scale empirical validity via a limited trial (n=9) analyzed using Pearson product-moment correlation in SPSS; (3) practicality; and (4) initial feasibility. Aiken V coefficients ranged from 0.938 to 1.000 across all 12 items (mean V=0.943, all items valid). Pearson correlation showed all 12 mission items valid (r > r-table=0.666). Practicality responses reached 88.9% (very practical). These findings confirm that the LKPD achieves content validity, empirical validity, practicality, and initial feasibility.